STRATEGI GURU DALAM PEMBELAJARAN BERDIFERENSIASI BERBASIS INKLUSI PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI PERSATUAN INDONESIA DI SEKOLAH DASAR - Luluk Lailatul Mukarromah; Aizza Naya Andina; Desy Elvira Wulandari; Mujtahidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of implementing inclusive learning that can accommodate the diversity of student characteristics through adaptive learning strategies. Differentiated learning is one approach that can be used to adjust the learning process based on student needs so that all students can be optimally involved in learning activities. This study aims to describe the implementation of differentiated learning on the Unity of Indonesia material in inclusive elementary school classes at each grade level, as well as to identify the forms of learning strategy adjustments applied by teachers based on student characteristics and needs. The study used a qualitative approach with a descriptive research type. The study was conducted at SDN Banyuajuh 2 with research subjects of teachers in grades I, IV, and VI. Data collection techniques were carried out through semi-structured interviews with data analysis using the Miles and Huberman interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers apply different differentiated learning strategies according to the characteristics and needs of students at each grade level. In lower grades, learning emphasizes individual assistance and emotional regulation, while in higher grades, it emphasizes strengthening social participation pthrough group activities. Research findings indicate that differentiated learning in inclusive education is not static, but evolves according to the developmental needs of students. Therefore, the implementation of differentiated learning focuses not only on academic aspects but also considers the social and emotional aspects of students in inclusive learning.